2007
DOI: 10.1172/jci32373
|View full text |Cite|
|
Sign up to set email alerts
|

An anticancer C-Kit kinase inhibitor is reengineered to make it more active and less cardiotoxic

Abstract: Targeting kinases is central to drug-based cancer therapy but remains challenging because the drugs often lack specificity, which may cause toxic side effects. Modulating side effects is difficult because kinases are evolutionarily and hence structurally related. The lack of specificity of the anticancer drug imatinib enables it to be used to treat chronic myeloid leukemia, where its target is the Bcr-Abl kinase, as well as a proportion of gastrointestinal stromal tumors (GISTs), where its target is the C-Kit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
152
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(159 citation statements)
references
References 31 publications
7
152
0
Order By: Relevance
“…If it protects cardiomyocytes from oxidant stress, then its inhibition by imatinib explains its toxic effect. Recently, a modification to the molecule of imatinib to include an additional target, JNK, led to significant reduction of cardiotoxicity without any negative effect in the drug's potency [15]. This reengineered molecule, WBZ_4 is a methylated variant of imatinib.…”
Section: Imatinib Mesylatementioning
confidence: 99%
“…If it protects cardiomyocytes from oxidant stress, then its inhibition by imatinib explains its toxic effect. Recently, a modification to the molecule of imatinib to include an additional target, JNK, led to significant reduction of cardiotoxicity without any negative effect in the drug's potency [15]. This reengineered molecule, WBZ_4 is a methylated variant of imatinib.…”
Section: Imatinib Mesylatementioning
confidence: 99%
“…Incidence of cardiotoxicity was cited as similar to onset of heart failure incidence in the general population, estimated at 0.2% per year, as evidenced by new-onset heart failure or left ventricular dysfunction [5]. While the impact of imatinib cardiotoxicity for GIST has been debated, molecular re-engineering of anticancer C-kit kinase inhibitors and cellular data on mitochondrial dysfunction and adenosine triphosphate (ATP) production deficit in murine models suggest a relationship, despite advocates for imatinib safety [1114]. Prospective data on cardiac function and long-term follow-up data are needed to confirm murine observation in humans.…”
Section: Discussionmentioning
confidence: 99%
“…As noted in 2007 [4], labile hydration patterns in the target protein provide suitable "epistructural" (around the structure) blueprints. Thus, it has been shown that water becomes easily removable when found in the vicinity of certain packing defects in proteins known as dehydrons [1].…”
mentioning
confidence: 99%
“…Lead optimization has been increasingly influenced by the identification of labile water molecules at the interface with the target protein [4][5][6][7]. These molecules are expected to be displaced upon drug binding.…”
mentioning
confidence: 99%
See 1 more Smart Citation